2018
DOI: 10.1177/2047487318811956
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and significance of T-wave inversion in Arab and Black paediatric athletes: Should anterior T-wave inversion interpretation be governed by biological or chronological age?

Abstract: Background: International electrocardiographic (ECG) recommendations regard anterior Twave-inversion (ATWI) in athletes <16 years to be normal. Design: Identify the prevalence, distribution, and determinants of TWI by ethnicity, chronological and biological age within paediatric athletes. Secondly, establish diagnostic accuracy of international ECG recommendations against refinement within athletes who present ECG variants isolated to ATWI (V1-V4) using receiver operator curve (ROC) analysis. Clinical context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…and reported that 15.8% presented anterior TWI, in the majority of cases confined to leads V1 to V3. 33 In this study, the prevalence of anterior TWI and of Jt elevation was higher in Arabic athletes aged <16 years and in black athletes. Of notice, in three black athletes, a cardiac disease was diagnosed; in these cases, TWI in leads V1 to V4 was associated with other abnormal features, such as lateral TWI, Q waves, or wide QRS.…”
Section: Black Athletesmentioning
confidence: 48%
“…and reported that 15.8% presented anterior TWI, in the majority of cases confined to leads V1 to V3. 33 In this study, the prevalence of anterior TWI and of Jt elevation was higher in Arabic athletes aged <16 years and in black athletes. Of notice, in three black athletes, a cardiac disease was diagnosed; in these cases, TWI in leads V1 to V4 was associated with other abnormal features, such as lateral TWI, Q waves, or wide QRS.…”
Section: Black Athletesmentioning
confidence: 48%
“…Overall, McClean and collaborators have opened a door to improve the predictive power and accuracy of current ECG criteria, particularly in children. 8 Nevertheless, applicability in clinical practice still needs to be established. Chronological age is easily assessed in most individuals but the maturity stage (i.e.…”
Section: Should Biological Age-determination Be Incorporated Into CLImentioning
confidence: 99%
“…As McClean and collaborators suggest, looking at bones may better discriminate the significance of TWI in young individuals than checking an identity card for their chronological age. 8…”
Section: A Path Towards Personalised Medical Decisionsmentioning
confidence: 99%
See 2 more Smart Citations